POSTINJECTION CONTRACTURE OF THE MANDIBLE - Fattayeva Dilorom Rustamovna, Karimboev Izzatillo Allanazar ugli, Otakhonov Ruzibek Oripjon ugli, Ergashev Jaloliddin Tojiyevich (Journals Park Publishing, 2022)
The relevance of the topic. Local anesthesia in dentistry can currently be considered as a separate discipline of dentistry. As experience shows, anesthesia has been and remains one of the most important problems, both in general dentistry and in its private sections.
Keywords: Anesthesia, post-injection contracture, mandible, X-ray examination